(untitled) (Zoological Records and Reviews, 2024)
Wetlands are among the most biodiverse and ecologically productive ecosystems on Earth, yet they continue to be lost at rates three times higher than forests globally. This study quantifies the conservation importance of wetlands for faunal diversity across four wetland types – natural fens, managed reedbeds, restored peatlands, and floodplain forests – in Sweden, Denmark, and the Netherlands, using multi-taxon biodiversity surveys (waterbirds, macroinvertebrates, amphibians, dragonflies; n = 16,847 individual records across 284 taxa) at 54 wetland sites of varying condition and management history (2021-2023). Wetland condition index (WCI, 0-100) was the strongest predictor of multi-taxon species richness across all four taxonomic groups (linear mixed model beta = 0.58 +- 0.07, p < 0.001). Natural fens supported the highest mean species richness across all groups (waterbirds 18.4 +- 2.1 species, amphibians 5.8 +- 0.9, dragonflies 24.8 +- 3.2, macroinvertebrates 42.4 +- 4.8), while degraded peatlands showed the greatest depletions relative to near-natural reference conditions. Functional diversity (FRic) was positively correlated with WCI (r = 0.74, p < 0.001) and declined more steeply than taxonomic richness across the condition gradient. Restored wetlands (post-restoration age 5-18 years) recovered to 72.4 +- 8.4% of reference wetland species richness, with waterbirds and dragonflies recovering faster than amphibians and macroinvertebrates. Carbon stock analysis confirmed that near-natural fens sequester 4.8-fold more carbon per ha than degraded sites, establishing a strong biodiversity-carbon co-benefit nexus for wetland restoration. These findings provide quantitative benchmarks for wetland restoration target-setting under EU Nature Restoration Law Article 11 (peatland and wetland targets) and the Ramsar Convention Programme.